Imaging in Patients with Bisphosphonate-Associated Osteonecrosis of the Jaws (MRONJ) - Britt-Isabelle Berg; Andreas A. Mueller; Marcello Augello; Scott Berg; Claude Jaquiéry (Dentistry Journal, 2016)
Background: Bisphosphonate-associated osteonecrosis of the jaws (MRONJ/BP-ONJ/BRONJ) is a commonly seen disease. During recent decades, major advances in diagnostics have occurred. Once the clinical picture shows typical MRONJ features, imaging is necessary to determine the size of the lesion. Exposed bone is not always painful, therefore a thorough clinical examination and radiological imaging are essential when MRONJ is suspected. Methods: In this paper we will present the latest clinical update on the imaging options in regard to MRONJ: X-ray/Panoramic Radiograph, Cone Beam Computed Tomography (CBCT) and Computed Tomography (CT), Magnetic Resonance Imaging (MRI), Nuclear Imaging, Fluorescence-Guided Bone Resection. Conclusion: Which image modality is chosen depends not only on the surgeon’s/practitioner’s preference but also on the available imaging modalities. A three-dimensional imaging modality is desirable, and in severe cases necessary, for extended resections and planning of reconstruction.